Price Formation and Market Quality When the Number and Presence of Insiders Is Unknown - Schnitzlein, Charles R. (Review of Financial Studies, 2002)
In most models of market microstructure tractability requires that all market participants know the number (and presence) of competing insiders. I drop this assumption in experimental asset markets. Outcomes are qualitatively consistent with theoretical models when the number of insiders is disclosed prior to trade. When it is not, insiders use the timing and size of trades interactively to hide from the dealers and each other, dealers have difficulty identifying insider trades, and liquidity patterns do not differ as a function of the number of insiders. In general, insider behavior has strategic dimensions not admitted in Kyle (1985) and extensions. Copyright 2002, Oxford University Press.